(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2025)
This article presents an experience report on the staging of a shadow theater show that addresses the theme of migration and the contemporary global crisis. The production was carried out by Voeverá Theater Company of Chapecó (SC), under the direction of Alexandre Fávero, from Cia Teatro Lumbra (RS). The study details the creative and collaborative process, from the conception of the idea to the materialization of the show, exploring the expressive potential of shadow theater to raise awareness among the public about the complexity and urgency of migration issues. The analysis focuses on the aesthetic and narrative choices, the interaction between artists from the different companies and the challenges and lessons learned from the staging experience. Through a detailed description of the process, the article seeks to contribute to the reflection on the role of theater as a tool for social engagement and to the understanding of the dynamics of collaborative stage creation in the context of group theater. [1] Voeverá Theater Company, founded in 1987, in Chapecó, Santa Catarina. [2] Set designer, researcher, director and stage director. [3] Lumbra Theater Company - collective from Porto Alegre, Rio Grande do Sul, Brazil.